Restoration treatments in urban park forests drive long‐term changes in vegetation trajectories. Issue 3 (26th April 2016) - Johnson, Lea R.; Handel, Steven N.
Abstract: Municipalities are turning to ecological restoration of urban forests as a measure to improve air quality, ameliorate urban heat island effects, improve storm water infiltration, and provide other social and ecological benefits. However, community dynamics following urban forest restoration treatments are poorly documented. This study examines the long‐term effects of ecological restoration undertaken in New York City, New York, USA, to restore native forest in urban park natural areas invaded by woody non‐native plants that are regional problems. In 2009 and 2010, we sampled vegetation in 30 invaded sites in three large public parks that were restored 1988–1993, and 30 sites in three large parks that were similarly invaded but had not been restored. Data from these matched plots reveal that the restoration treatment achieved its central goals. After 15–20 years, invasive species removal followed by native tree planting resulted in persistent structural and compositional shifts, significantly lower invasive species abundance, a more complex forest structure, and greater native tree recruitment. Together, these findings indicate that successional trajectories of vegetation dynamics have diverged between restored forests and invaded forests that were not restored. In addition, the data suggest that future composition of these urban forest patches will be novel assemblages. Restored and untreated sites shared a suite of shade‐intolerant, quickly‐growing tree species that colonize disturbed sites, indicating that restoration treatments created sites hospitable for germination and growth of species adapted to high light conditions and disturbed soils. These findings yield an urban perspective on the use of succession theory in ecological restoration. Models of ecological restoration developed in more pristine environments must be modified for use in cities. By anticipating both urban disturbances and ecological succession, management of urban forest patches can be adjusted to better predict and direct long‐term outcomes. An urban approach to ecological restoration must use realistic, flexible targets to preserve and enhance urban biodiversity for both short‐term benefits and long‐term sustainability.